Transverse momentum and process dependent azimuthal anisotropies in√sNN=8.16 TeV p+Pb collisions with the ATLAS detector - Aad, Georges; Dunford, Monica; Franchino, Silvia; Krishnan, Anjali; Kugel, Andreas; Napolitano, Fabrizio; Schöning, André; Schultz-Coulon, Hans-Christian; Spieker, Thomas; Stamen, Rainer; Starovoitov, Pavel; Weber, Sebastian; et al. (The European physical journal. C, Particles and fields, 2020)
The azimuthal anisotropy of charged particles produced in $$\sqrt{s_{NN}}=8.16$$sNN=8.16 TeV p+Pb collisions is measured with the ATLAS detector at the LHC. The data correspond to an integrated luminosity of 165 $$nb^{-1}$$nb-1 that was collected in 2016. Azimuthal anisotropy coefficients, elliptic $$v_2$$v2 and triangular $$v_3$$v3, extracted using two-particle correlations with a non-flow template fit procedure, are presented as a function of particle transverse momentum ($$p_T$$pT) between 0.5 and 50 GeV. The $$v_2$$v2 results are also reported as a function of centrality in three different particle $$p_T$$pT intervals. The results are reported from minimum-bias events and jet-triggered events, where two jet $$p_T$$pT thresholds are used. The anisotropies for particles with $$p_T$$pT less than about 2 GeV are consistent with hydrodynamic flow expectations, while the significant non-zero anisotropies for $$p_T$$pT in the range 9-50 GeV are not explained within current theoretical frameworks. In the $$p_T$$pT range 2-9 GeV, the anisotropies are larger in minimum-bias than in jet-triggered events. Possible origins of these effects, such as the changing admixture of particles from hard scattering and the underlying event, are discussed.